EFEKTIFITAS IKLAN GO-JEK PENGGUNA MEDIA SOSIAL KOTA PADANG - Tri Irfa Indrayani; Asrizal Asrizal; Nurdiah Shalat (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2020)
Abstract : Research Objectives to measure and analyze the effectiveness of Go-Jek online advertising on social media. This study uses a sample to residents who live in Padang City and are social media users. Sampling was done by Purpose sampling with 100 respondents. The data analysis technique used is the EPIC method, which consists of; empathy (empathy), persuasion (persuasion), impact (impact), and communication (communication). The EPIC analysis results partially for each variable are in the